Optimizing shift scheduling and work-life balance to improve job satisfaction among female nurses - Rohita, Tita; Nursalam, Nursalam; Yetti, Krisna; Kuntarti, Kuntarti; Nurkholik, Dedeng; Hasanah, Idyatul (Gaceta Médica de Caracas, 2022)
Introduction: Among the numerous factors that can improve job satisfaction are challenging work, rewards that meet employees’ expectations, a comfortable working environment, and a balance between personal life and work (work-life balance). This study analyzed the relationship between shift schedule arrangement and work-life balance among female nurses and its impact on job satisfaction.